Surgical treatment of tumors and spondylitis of the cervical spine in children: what does 20-year monocentric experience with the syndromic approach reveal? - D.A. Glukhov; A.Yu. Mushkin (Хирургия позвоночника, 2025)
Objective. To analyze short- and long-term results of surgical treatment of children with tumor and infectious destruction of the cervical vertebrae. Material and Methods. The study included data from 94 children. The following parameters were evaluated: the effectiveness of perioperative use of halo-fixation, surgical approaches, methods of reconstruction and stabilization of the spine, dynamics of pain syndrome and neurological disorders, and the structure of postoperative complications. The material was statistically processed using nonparametric analysis methods. Statistical analysis and visualization of the obtained results were carried out using the R programming language. Results. A halo-fixation was used in 12.8 % of cases due to significant deformations and stenosis of the spinal canal. Of the 34 resections that required combined approach, 30 were performed in a single surgical session. The median duration of the surgical stage was 162.5 minutes, the median blood loss volume – 100 ml. Reconstruction of the anterior column of the spine was required in 62.8 % of cases, and posterior instrumental fixation – in 42.6 %. Local pain syndrome was eliminated in all cases. Four patients with neurological disorders showed an improvement in neurological status by one or more levels according to the Frankel scale, two patients – worsening by one level, and no significant change in the neurological picture was observed in nine cases. Complications were revealed in 26.6 % of cases, while only five patients required repeated surgery. The outcome of surgical treatment is affected by the destruction of three or more vertebrae (p = 0.0298). Conclusion. In the treatment of children with cervical vertebrae destruction, a unified syndromic approach is justified and associated with a minimal frequency of clinically significant perioperative complications.